2010
DOI: 10.1152/ajpregu.00016.2010
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm muscle shortening modulates kinematics of lower rib cage in dogs

Abstract: We tested the hypothesis that diaphragm muscle shortening modulates volume displacement and kinematics of the lower rib cage in dogs and that posture and mode of ventilation affect such modulation. Radiopaque markers were surgically attached to the lower three ribs of the rib cage and to the midcostal region of the diaphragm in six dogs of ∼8 kg body masses, and the locations of these markers were determined by a biplane fluoroscopy system. Three-dimensional software modeling techniques were used to compute vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
3
1
Order By: Relevance
“…Our data suggest that at higher lung volumes and greater levels of muscle activation, posture continues to be an important determinant of lower rib cage kinematics. In contrast to our diaphragm rib cage VD data, Chu et al (6) showed that the lower ribs displaced greater volume in the prone than the supine posture. However, their VD component is the combination of three different rotations around the spinal axis, and there may be greater cephalic displacement of the lower ribs in the prone posture causing the large diaphragm rib cage VD component shown in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our data suggest that at higher lung volumes and greater levels of muscle activation, posture continues to be an important determinant of lower rib cage kinematics. In contrast to our diaphragm rib cage VD data, Chu et al (6) showed that the lower ribs displaced greater volume in the prone than the supine posture. However, their VD component is the combination of three different rotations around the spinal axis, and there may be greater cephalic displacement of the lower ribs in the prone posture causing the large diaphragm rib cage VD component shown in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…During higher levels of diaphragm activation, the height of the zone of apposition of the diaphragm decreases markedly so that most of the lower rib cage becomes exposed to the expiratory effect of pleural pressure, rather than the inspiratory effect of abdominal pressure. However, during bilateral maximal phrenic nerve stimulation, this inspiratory effect appears to be absent, and the rib cage moves inward and caudally, consistent with the absent rib cage VD component shown in this study and decreased rib VD found previously (6). This is also consistent with a study by Krayer et al (13), who suggested that diaphragm shortening had no inspiratory effect on the rib cage during maximal stimulation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…If so, they shared a mammalian developmental innovation with significant functional correlates. In living mammals, rotation of the ribs at the rib/sternebral junctions and between adjacent sternebrae are important components of expansion of the rib cage during ventilation (Chu et al ., 2010; Gao et al ., 2016, Beyer et al ., 2014). In this way, an evolutionary change in the location of the LSF may be tentatively tied to a structural and functional innovation that facilitates mammalian ventilation.…”
Section: The Lateral Presternal Element and The Lateral Somitic Frontiermentioning
confidence: 99%
“…Several studies have focused on biomechanical modelling of breathing [2][3][4], but the experimental study of breathing presents several challenges. For instance, the changes in rib cage volume and shape during the breathing cycle are often analysed experimentally using only external measurements, in vitro approaches or animal models [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%